Human rights advocacy stories - Hurwitz, Deena; Satterthwaite, Margaret L. (New York : Foundation Press ; [St. Paul, MN] : Thomson/West, 2009)
This book tells the story of fifteen human rights cases from around the world?including cases adjudicated by a court or commission as well as controversies decided outside the courthouse. The cases illustrate key themes, including: the development of human rights norms and the work of human rights organizations; the function of individual and collective identities in human rights struggles; the role of international criminal norms in protecting human rights; globalization, foreign policy, and the economy; and human rights in a world at war. By making real the stories of collective action behind human rights advocacy, legal norms, and enforcement mechanisms, Human Rights Advocacy Stories illustrates the dynamic interactions between advocacy and legal doctrine.--
Outlawing torture: the story of Amnesty International's efforts to shape the U.N. convention against torture / Jayne Huckerby and Sir Nigel Rodley -- The story of the TAC case: the potential and limits of socio-economic rights litigation in South Africa / Amy Kapczynski and Jonathan M. Berger -- The stories of Dudgeon and Toonen: personal struggles to legalize sexual identities / Mark Bromley and Kristen Walker -- Gaining legal recognition of indigenous land rights: the story of the Awas Tingni case in Nicaragua / S. James Anaya and Maia S. Campbell -- The law of the republic versus the "law of the brothers": a story of France's law banning religious symbols in public schools / Karima Bennounce -- Engendering genocide: the Akayesu case before the International Criminal Tribunal for Rwanda / Beth Van Schaack -- The story of Samuel Hinga Norman in Sierra Leone: can truth commissions and criminal prosecutions coexist after conflict? / Ari S. Bassin and Paul Van Zyl -- Universal jurisdiction and the dilemmas of international criminal justice: the Sabra and Shatila case in Belgium / Deena R. Hurwitz -- Arresting juxtapositions: the story of Roper v. Simmons / Alison J. Nathan -- The story of Narmada Bachao Andolan: human rights in the global economy and the struggle against the World Bank / Smita Narula -- r Doug Ford -- The story of Hamid Karzai: the paradoxes of state-building and human rights / Aziz Z. Huq -- The story of El-Masri v. Tenet: human rights and humanitarian law in the "war on terror" / Margaret L. Satterthwaite.
At head of title: Foundation Press
Includes bibliographical references.
Keywords: Human rights advocacy; Human rights; Human rights; Human rights advocacy; Menschenrecht; Aufsatzsammlung